2023
DOI: 10.1049/ipr2.12736
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lung scan imaging using deep multi‐task learning structure for Covid‐19 disease

Abstract: Covid‐19 caused by the SARS‐CoV2 virus has become a pandemic all over the world. By growing in a number of cases, there is a need for clinical decision‐making system based on machine learning models. Most of the previous studies have examined only one task, while the detection and identification of infectious area are conducted simultaneously in the real world. Thus, the present study aims to propose a multi‐task model which can perform automatic classification‐segmentation for screening Covid‐19 pneumonia by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, further study is required to examine how various medical pictures affect classification accuracy. Kordnoori et al [46] suggested a deep multitask learning model that can automatically classify and segment lung tissue to screen for Covid-19 pneumonia using chest CT imaging. U-NET architecture was adopted in the proposed method, including ten fully connected layers in the decoder, ten convolutional layers in the common encoder, and ten layers in the perceptron.…”
Section: Related Workmentioning
confidence: 99%
“…However, further study is required to examine how various medical pictures affect classification accuracy. Kordnoori et al [46] suggested a deep multitask learning model that can automatically classify and segment lung tissue to screen for Covid-19 pneumonia using chest CT imaging. U-NET architecture was adopted in the proposed method, including ten fully connected layers in the decoder, ten convolutional layers in the common encoder, and ten layers in the perceptron.…”
Section: Related Workmentioning
confidence: 99%
“…Kordnoori et al. [15] proposed a multi‐task model with two main tasks of classification and segmentation. Their model contained one common encoder between tasks for representing features.…”
Section: Related Workmentioning
confidence: 99%
“…Lung segmentation, a vital stage in the automated processing of lung scan pictures, is the subject of Kordnoori et al [20]. The suggested method makes use of a DL framework that combines numerous related tasks, allowing for collaborative learning and information exchange between various parts of lung study.…”
Section: Literature Reviewmentioning
confidence: 99%